Heteroatom dopings and hierarchical pores of graphene for synergistic improvement of lithium–sulfur battery performance. Issue 5 (23rd March 2018) - Li, Jiahui; Xue, Caining; Xi, Baojuan; Mao, Hongzhi; Qian, Yitai; Xiong, Shenglin
Abstract : Lithium–sulfur batteries: Both the cycling stability and rate capability are adequately enhanced due to the synergistic effect of heteroatom dopings and hierarchical pores of carbon matrix, guiding the design of advanced scaffolds towards high-performance lithium–sulfur batteries. Abstract : Lithium–sulfur batteries have attracted wide research interest due to their high specific capacity (1675 mA h g −1 ) and high specific energy (2500 W h kg −1 ). Herein, the two-dimensional nitrogen/sulfur synchronous-doped few-layer graphene (N, S-FLG) was prepared by a simple calcination route at 900 °C under an argon atmosphere with g-C3 N4 as a structural template. The calcination temperature favorably adjusted the doping levels and surface texture of the as-obtained samples. Relying on the synergistic interaction of the structural traits, as the reservoir of sulfur, NS-FLG-900 (calcination temperature 900 °C) can maintain a reversible capacity of 602 mA h g −1 after 300 cycles at a current density of 0.8 A g −1 and 506.4 mA h g −1 after 500 cycles at a current density of 1.6 A g −1 . The outstanding performance is obtained due to the synergistic effect of the introduction of N and S into the carbon lattice, the high pore volume (1.31 cm 3 g −1 ) and large specific surface area (460.9 m 2 g −1 ).